Pengaruh Kebijakan Pengelolaan Risiko Terhadap Keputusan Investasi Dan Keuangan Perusahaan - Hayati Eka Pratiwi; Sulvi Andini Br Butar Butar; Amelia Ardan Tambunan; Rahmat Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Risk management policies play an important role in influencing a company's investment and financial decisions. The aim of this research is to analyze the influence of implementing risk management policies on investment and company financial decisions. Literature study analysis of financial data and related data from several companies that implement risk management policies is used as a research method. The research results show that effective risk management practices can improve a company's investment decisions by reducing uncertainty and increasing investor confidence. Apart from that, good risk management policies also have a positive impact on company financial decisions, such as more efficient cash management, better cost management, and improved overall financial performance. These findings provide an important contribution for practitioners and researchers to understand the importance of implementing risk management policies in the context of corporate investment and financial decisions. The practical significance of this research is the need for companies to pay attention.